Evaluating the message of an ongoing communication campaign to reduce the duration of untreated psychosis in a Latinx community in the United States. Issue 2 (25th March 2021) - Calderon, Vanessa; Cain, Rosalba; Torres, Eva; Lopez, Steven R.
Abstract: Aim: Initiatives aimed at reducing the duration of untreated psychosis (DUP) attempt to increase the community's level of psychosis literacy. Most of these efforts, however, have failed to reduce DUP. One plausible explanation is that the campaigns do not actually increase psychosis literacy. To date, there have been few efforts to assess whether the campaign messaging does indeed increase psychosis literacy prior to or during the campaign. This study evaluated whether the message of the La CLAve DUP reduction program delivered during the campaign increased the psychosis literacy of a U.S. Latinx community. Methods: The sample consisted of 81 Latinx community residents aged 15–84. Two community health educators of the La CLAve campaign facilitated workshops using a narrative film to initiate a conversation in the community about the signs of psychosis and the importance of professional help‐seeking early in the illness course. Psychosis literacy was assessed via questionnaires pertaining to a hypothetical vignette administered before and after the workshops. Results: The psychosis literacy of participants increased after the workshops in several domains. Participants' knowledge of multiple psychotic symptoms, self‐efficacy in their ability to recognize psychosis in others, and correct attributions of a hypothetical vignette's psychotic symptoms significantly increased. No changes were observed in recommendations for professional help‐seeking. Conclusions: These findings provide support for the effectiveness of the La CLAve messaging in increasing psychosis literacy of U.S. Latinx community residents. Evidence‐based campaign messaging is needed to increase the success of DUP reduction programs especially among underserved communities.